(untitled) (Research, Society and Development, 2022)
Transgenderism refers to the condition in which biological sex and gender are not compatible. Currently, Brazil is at the top of the ranking of countries that perform the most aesthetic surgeries, among them, facial feminization surgery (FFC). The present study seeks to carry out a survey in the literature to assess the influence of facial feminization surgeries on forensic dental identification. It was carried out based on scientific studies published and indexed in Pubmed/MEDLINE, Lilacs, BVS and Scielo databases. It is necessary for the professional to understand the different male and female facial features. Furthermore, with regard to identification, it depends on the determination of the four major human characteristics: ethnicity, sex, age and height, with the determination of these characteristics, the number of individuals to be researched is reduced. However, in the case of transsexuals, a description of their physical remains, including biological sex, may have little correlation with their social identity, delaying and often confusing the issue of identification. Therefore, facial feminization can influence human identification. Thus, it is crucial that forensic dentists are able to identify and discern these changes when faced with these situations.